Estudio del arreglo estructural de las proteínas SCHR de Bacillus subtilis 168 - Martínez Valencia, Rene (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
The chromate transporter superfamily (CHR) is divided into two families according to its size: long-chain or two-domain proteins (LCHR) and short-chain or monodomain proteins (SCHR), the latter divided into three subfamilies ( SCHR1-SCHR3). The chr3N and chr3C genes of Bacillus subtilis 168 encode homologous proteins of the SCHR3 subfamily, which have been proposed to form antiparallel heterodimers to confer chromate resistance. To date there are no reports about the structural arrangement of homologous proteins belonging to the SCHR subfamily. The objective of this work was to determine the membrane topology of the Chr3N and Chr3C protein pair by using translational fusions in hydrophilic regions of the Chr3N and Chr3C proteins with the phoA and LacZ reporter genes. Thirteen translational fusions were constructed in the pUCPphoA vector and seven fusions in the pUCPlacZ vector. Fusions were measured for enzymatic activity in Escherichia coli CC118. The results of activity in the Chr3N protein allowed to establish a topological model of five transmembrane segments (STM) connected by two periplasmic and two cytoplasmic handles, with their amino terminal end in the periplasm and their carboxyl end in the cytoplasm. On the other hand, in the Chr3C protein, a topology of five STMs connected by two periplasmic and two cytoplasmic handles was determined, with the amino terminal end located in the cytoplasm and the carboxyl terminal end in the periplasm. These results indicate an antiparallel arrangement of the STMs of Chr3N and Chr3C. An antiparallel membrane topology suggests that the amino and carboxyl halves of the transporter perform a different function.

La superfamilia de transportadores de cromato (CHR) se divide en dos familias de acuerdo a su tamaño: proteínas de cadena larga o bidominio (LCHR) y proteínas de cadena corta o monodominio (SCHR), esta última dividida a su vez en tres subfamilias (SCHR1-SCHR3). Los genes chr3N y chr3C de Bacillus subtilis 168 codifican proteínas homólogas de la subfamilia SCHR3, las cuales se ha propuesto que forman heterodímeros antiparalelos para conferir resistencia a cromato. Hasta la fecha no existen reportes acerca del arreglo estructural de proteínas homólogas pertenecientes a la subfamilia SCHR. El objetivo de este trabajo fue determinar la topología membranal de la pareja de proteínas Chr3N y Chr3C mediante el uso de fusiones traduccionales en regiones hidrofílicas de las proteínas Chr3N y Chr3C con los genes reporteros phoA y LacZ. Se construyeron trece fusiones traduccionales en el vector pUCPphoA y siete fusiones en el vector pUCPlacZ. A las fusiones se les midió la actividad enzimática en Escherichia coli CC118. Los resultados de actividad en la proteína Chr3N permitieron establecer un modelo topológico de cinco segmentos transmembranales (STM) conectados por dos asas periplásmicas y dos asas citoplásmicas, con su extremo amino terminal en el periplasma y su extremo carboxilo terminal en el citoplasma. Por su parte, en la proteína Chr3C se determinó una topología de cinco STM conectados por dos asas periplásmicas y dos asas citoplásmicas, con el extremo amino terminal localizado en el citoplasma y el extremo carboxilo terminal en el periplasma. Estos resultados indican un arreglo antiparalelo de los STM de Chr3N y Chr3C. Una topología de membrana antiparalela sugiere que las mitades amino y carboxilo del transportador llevan a cabo una función diferente.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2011-0003; Arreglo estructural; Proteínas; SCHR; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3866